Weight-bearing in ankle fractures: An audit of UK practice. (June 2019) - ,; Gill, James R.; Lostis, Emilie; Bleibleh, Sabri S.; Hennessy, Michael S.; Thondickal, Femi; Gadd, Richard J.; Grupping, Rachael; Chikate, Albert; Khor, Suan; Malani, Sangam; Nabulyato, William; et al.
Graphical abstract: Highlights: The standard of care for weight-bearing after ankle fracture was previously unknown. 81% of non-operatively managed patients with uni-malleolar fractures are advised early weight-bearing. 21% of operatively managed patients are advised early weight-bearing. There is community equipoise and a randomized study examining weight-bearing in ankle fractures is feasible. Abstract: Introduction: The purpose of this national study was to audit the weight-bearing practice of orthopaedic services in the National Health Service (NHS) in the treatment of operatively and non-operatively treated ankle fractures. Methods: A multicentre prospective two-week audit of all adult ankle fractures was conducted between July 3rd 2017 and July 17th 2017. Fractures were classified using the AO/OTA classification. Fractures fixed with syndesmosis screws or unstable fractures (>1 malleolus fractured or talar shift present) treated conservatively were excluded. No outcome data were collected. In line with NICE (The National Institute for Health and Care Excellence) criteria, "early" weight-bearing was defined as unrestricted weight-bearing on the affected leg within 3 weeks of injury or surgery and "delayed" weight-bearing as unrestricted weight-bearing permitted after 3 weeks. Results: 251 collaborators from 81 NHS hospitals collected data: 531 patients were managed non-operatively and 276 operatively. The mean age was 52.6 years and 50.5 respectively. 81% of non-operatively managed patients were instructed for early weight-bearing as recommended by NICE. In contrast, only 21% of operatively managed patients were instructed for early weight-bearing. Discussion: The majority of patients with uni-malleolar ankle fractures which are managed non-operatively are treated in accordance with NICE guidance. There is notable variability amongst and within NHS hospitals in the weight-bearing instructions given to patients with operatively managed ankle fractures. Conclusion: This study demonstrates community equipoise and suggests that the randomized study to determine the most effective strategy for postoperative weight-bearing in ankle fractures described in the NICE research recommendation is feasible.